Impact evaluation: assessing the impact of policy-oriented social science research - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
Economists have engaged for some time in developing methodologies for assessing the economic impact of agricultural research and in undertaking empirical studies to measure this impact.1 In recent years they have documented more than 1,800 estimates of rates of return to agricultural research. Economists have paid little attention, however, to how to evaluate the impact of social science research. A symposium conducted by the International Food Policy Research Institute in 1997 was one of the first attempts to address this knowledge gap. In November 2001 the Netherlands Ministry of Foreign Affairs and IFPRI brought together a group of researchers to follow up on the earlier symposium. Their conclusions fall into two broad categories: how to measure or value the economic impact of policy-oriented social science research and how to enhance the effectiveness of such research in policymaking environments. This brief summarizes the key elements of the work of the conference.